2017
DOI: 10.1590/0103-6440201601454
|View full text |Cite
|
Sign up to set email alerts
|

Repair of Bone Defects with Chitosan-Collagen Biomembrane and Scaffold Containing Calcium Aluminate Cement

Abstract: Innovative biomaterials can provide a promising new direction for the treatment of bone defects, stimulating a proper repair process, with no damage to adjacent tissues. The purpose of this in vivo study was to evaluate the biocompatibility and the osteoinductive capacity of chitosan-collagen biomembrane and scaffold containing calcium aluminate cement. Eighteen New Zealand white rabbits (Oryctolagus cuniculus) were distributed according to the experimental times of analysis (7, 15 and 30 days). Four bone defe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 21 publications
0
14
0
3
Order By: Relevance
“…The authors also showed that CHAlCa scaffold acts as a biocompatible and bioactive matrix, since cell proliferation, ALP activity, DSPP mRNA expression and calcium-rich matrix deposition were significantly enhanced in those HDPCs seeded onto its structure. The bioactive potential of CHAlCa may be related to the hydration process of AlCa cement when in contact with humidity, releasing Ca²+ and Al³+ ions over a long period of time (15). It has been shown that CHAlCa scaffold is capable of releasing Ca²+ when immersed in water, leading to the establishment of an alkaline (pH=9.0) environment within 24 h, followed by a stabilization (pH =7.8) up to 7 days (9).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors also showed that CHAlCa scaffold acts as a biocompatible and bioactive matrix, since cell proliferation, ALP activity, DSPP mRNA expression and calcium-rich matrix deposition were significantly enhanced in those HDPCs seeded onto its structure. The bioactive potential of CHAlCa may be related to the hydration process of AlCa cement when in contact with humidity, releasing Ca²+ and Al³+ ions over a long period of time (15). It has been shown that CHAlCa scaffold is capable of releasing Ca²+ when immersed in water, leading to the establishment of an alkaline (pH=9.0) environment within 24 h, followed by a stabilization (pH =7.8) up to 7 days (9).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that CHAlCa scaffold is capable of releasing Ca²+ when immersed in water, leading to the establishment of an alkaline (pH=9.0) environment within 24 h, followed by a stabilization (pH =7.8) up to 7 days (9). A number of studies demonstrated that Ca²+ gradient exerts chemotactic, proliferative, and bioactive effects on MSCs (7,8,15). In these studies, the authors reported that a slightly alkaline environment (pH 8.0-9.0) favors odontoblastic differentiation of pulp cells.…”
Section: Discussionmentioning
confidence: 99%
“…Chitosan is a cationic polysaccharide, deriving from chitin deacetylation, which has gained a prominent place in biomedicine for a wide range of applications including drug delivery, wound dressings, bacterial contamination control, fat binding, and tissue engineering [1,2,3,4,5]. The peculiarity of chitosan, compared to other polysaccharides, is that it has been shown to provoke minimal or no foreign-body reaction, including inflammatory response and fibrotic encapsulation when used in hydrogel systems [6,7], polyelectrolyte multilayers [8], biomembranes [9] and as a porous 3-D scaffold [10]. Besides, chitosan has been shown to promote cell adhesion and proliferation in tissue engineering applications, especially when applied for bone tissue regeneration where it showed osteoconductivity and ability to promote osteogenic differentiation [11,12,13,14,15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Moraes et al 14 estudaram o reparo ósseo em defeitos na calvária de coelhos, em quatro grupos de intervenção: um com biomembrana de quitosana, outro com um scaffolds de aluminato de cálcio, um grupo controle e um com osso autólogo. No entanto diferente do que foi relatado no estudo de Chen et al 12 , o autor encontrou que a biomembrana de quitosana obteve menor cicatrização óssea entre os grupos.…”
Section: Discussionunclassified